Chapter La terminologia della salute e sicurezza sul lavoro in tedesco per l'Alto Adige - Stanizzi, Isabella (Proceedings e report, 2021)
The paper deals with the German language terminology of occupational health and safety (OHS) in South Tyrol, Italy, where the minority language has official status next to the national language. The South Tyrolean German legal language is developed along two main lines, i.e. through secondary term formation based on translations of Italian terms or by adopting terms already established in the German-speaking countries. The examples given in the paper show the presence of terminological gaps in South Tyrolean German, the influence of Italian, the delicate relation with the legal terminology of the foreign German-speaking legal systems and the difficulty of disseminating an unambiguous terminology in the domain of OHS at local level. The final part explains the currently adopted development and dissemination strategies.